Belgium : Report on Observance of Standards and Codes; Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The basic government finance processes are supported by a sound institutional and legal framework. Fiscal information is provided through regular publications and extensive use of the internet. Finally, audit processes are extensive and help improve budget management decisions, practices and standards, with government financial decisions evaluated ex ante and ex post by various institutions. Information is made available to the public on fiscal risk and tax expenditure in budget documents, in-year budgetary data on local government agency, content of final government accounts, and the governance of state-owned equity holdings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet